2010
DOI: 10.4055/cios.2010.2.3.148
|View full text |Cite
|
Sign up to set email alerts
|

Cotyloplasty in Cementless Total Hip Arthroplasty for an Insufficient Acetabulum

Abstract: BackgroundCotyloplasty is a technique that involves making a perforation of the medial wall of a shallow acetabulum and then inserting an acetabular cup with the medial aspect of its dome beyond the Kohler line. The purpose of this study was to evaluate the results of cementless total hip arthroplasty (THA) using cotyloplasty with focusing on the amount of medial cup protrusion.MethodsSixteen hips with insufficient acetabulum in sixteen patients were treated by cementless THA using cotyloplasty. The average pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 20 publications
0
17
0
2
Order By: Relevance
“…So, what rate of medial protrusion of the cup is the best? Dorr et al [23] recommended this rate should be less than 45% and Kim et al [24] suggested it should be within 50%-60%. Besides, according to Zha et al [8], a prospective 6-to 9-year follow-up of 43 consecutive patients using medial protrusio technique in cementless THA for DDH demonstrated that the rate of medial protrusion more than 60% had a high aseptic loosening rate in midterm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, what rate of medial protrusion of the cup is the best? Dorr et al [23] recommended this rate should be less than 45% and Kim et al [24] suggested it should be within 50%-60%. Besides, according to Zha et al [8], a prospective 6-to 9-year follow-up of 43 consecutive patients using medial protrusio technique in cementless THA for DDH demonstrated that the rate of medial protrusion more than 60% had a high aseptic loosening rate in midterm.…”
Section: Discussionmentioning
confidence: 99%
“…Inclination of cup is de ned as the angle between a horizontal line joining the ischial spines and a line parallel to the opening plane of the cup [22]. Rate of cup coverage and rate of medial protrusion are measured according to the methods introduced by Dorr et al [23] and Kim et al [24]. Rate of cup coverage is de ned as the ratio of degree of cup covered by the host bone and 180°( Fig.…”
Section: Radiological Assessmentsmentioning
confidence: 99%
“…Femoral stem osteolysis and radiolucencies were classified, as previously described by Gruen et al [13] Furthermore, the acetabular components were evaluated according to the DeLee and Charnley classification of acetabular osteolysis and radiolucencies [14]. Periprosthetic osteolysis is defined as a circular or oval area of distinct bone loss with a diameter of > 2 mm [15]. A radiolucent line between the implant and the surrounding bone, usually parallel to the implant surface.…”
Section: Methodsmentioning
confidence: 99%
“…Total hip arthroplasty (THA) in patients with DDH is technically demanding because of the altered hip anatomy. For acetabular reconstruction, the following techniques are described: (1) cranial positioning of the acetabular component (high hip center for steep acetabuli) [17, 31]; (2) medial protrusion technique (cotyloplasty for shallow acetabuli) [8, 19]; (3) customized acetabular augments (three-dimensional printing) [4] or high-porosity sockets such as Trabecular Metal, Regenerex, or Tritanium; (4) acetabular roof reconstruction with autologous bone grafting [33]; and (5) graft augmentation by rim mesh or hooked reinforcement ring devices with impaction morselized bone grafting [1, 15, 35]. In the first three techniques, however, acetabular bone stock is not preserved and the original hip center may be displaced.…”
Section: Introductionmentioning
confidence: 99%